STRATEGY TO IMPROVE THE QUALITY OF HUMAN RESOURCES (HR) THROUGH A TRAINING PROGRAM AT THE JOB TRAINING CENTER (BLK) EAST TANJUNG JABUNG REGENCY - Ade Elfhina; Annatun Nisa Mun'amah; Al-Munip; Haeran; Erwina Kartika Devi (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
This research is based on the low quality and skills of Human Resources (HR) which results in a large workforce in East Tanjung Jabung Regency who are still not working, which can be seen from BPS data of East Tanjung Jabung Regency regarding the Unemployment Rate in East Tanjung Jabung Regency. The formulation of the problem in this study is how the Strategy for Improving the Quality of Human Resources (HR) through a Training Program at the Job Training Center (Blk) of East Tanjung Jabung Regency. The research method used is qualitative. Data were collected through questionnaires (questionnaires), observations (observations) and documentation. The sampling method used is sensu which is carried out to the BLK (Job Training Center) and participants for each type of training carried out. The result of this research is that the development of human resources is generally indeed a must and need. Job training has an effect on the improvement and development of attitudes, ways of working, behavior, knowledge and skills as well as workers' morals so as to create good work performance and get optimal results for their well-being. The low educational background results in low competence so that there is a lack of expertise in work. Therefore, the role of the UPTD of the East Tanjung Jabung Regency Job Training Center is needed as one of the efforts to reduce the unemployment rate in East Tanjung Jabung Regency through its job training. Keywords: Use of Training, Improvement Strategy, Human Resources Quality, BLK